PENGARUH PEMBERIAN TEKNIK COUNTERPRESSURE TERHADAP PENURUNAN INTENSITAS NYERI PADA KALA I PERSALINAN DI RSUD SAWERIGADING PALOPO - Irmayanti. A.Oka (Voice of Midwifery, 2017)
The research aimed at investigating the effect of giving counterpressure technique to decrease the intensity of pain in the first stage of labor in the delivery room of RSUD Sawerigading Palopo. This study was conducted in a preexperimental manner with static group comparison design, in subject static group comparison design divided into two groups, where the treatment group was followed by observation and observation result compared with the observation result in the control group which only received standard treatment. Data were analyzed using T test. Where t value hit 6.971> t table 2.05, so it can be concluded that the results obtained mean that there is influence of counterpressure technique is big enough to decrease the intensity of labor pain. Keyword: Counterpressure, Labor Pain, Kala I